The Role of Research in Fisheries Management: The Conservation of Dolphins in the Eastern Tropical Pacific and the Exploitation of Southern Bluefin Tuna in the Southern Ocean - Harry Campbell, Samuel F. Herrick Jr., Dale Squires (Ocean development and international law, 2000)
This article uses two case studies to assess the role of research in policy formation and fishery management. One study focuses on measures to limit the mortality of dolphins taken when tuna are harvested in the eastern tropical Pacific. The other studies measures taken to limit harvests of Southern Bluefin Tuna. Both of these fisheries involve fugitive resources and transboundary resources spreading across both national exclusive economic zones and the high seas. Both fisheries were initially based on open access, but public policy has led to greater exclusive use through individual transferable quotas for Southern Bluefin Tuna and dolphin mortality limits. A number of policy conclusions are drawn.